The Effects of Rainfall and Terracing–Mulch Combinations on Soil Erosion in a Loess Hilly Area, China: Insights from Plot Simulations and WEPP Modeling - Michael Aliyi Ame; Wei Wei; Shuming Zhang; Wen Liu; Liding Chen (Land, 2025)
Soil erosion is a major environmental concern, especially in sensitive ecosystems like the Loess Plateau of China, where certain geological and climatic circumstances exacerbate the erosion process. Terracing and mulching are popular soil erosion management strategies in this region. However, their combined effects under varied rainfall intensities are poorly understood. The purpose of this study is to assess the performance of various terracing–mulch combinations in reducing water erosion under different rainfall intensities. The experimental layout included a control plot (C), non-terraced mulch applications (NTr-M), fish-scale pits with mulch (FSPs-M), zig terraces with mulch (ZTr-M), level bench terraces with mulch (LBTr-M), and trench terraces with mulch (TTr-M). Controlled artificial rainfall experiments were carried out under different intensities, and runoff and soil loss data were collected to evaluate the effects of the combinations. The event-based WEPP simulations, calibrated for the Loess Plateau, demonstrated strong predictive accuracy, as evidenced by the high correlation coefficients (R2 = 0.97 for runoff; R2 = 0.86 for soil loss) and Nash–Sutcliffe efficiency (NSE = 0.93 for runoff; NSE = 0.89 for soil loss), confirming their reliability in simulating erosion processes when compared to measured values. Our results revealed significant differences (p < 0.05) in mean runoff and soil loss among the treatments, ranked in the order LBTr-M < TTr-M < ZTr-M < FSPs-M < NTr-M < C. Incremental response analysis also revealed that the control plot (C) was the most sensitive to changes in rainfall intensity, followed by FSPs-M and NTr-M. In contrast, LBTr-M was found to be the most stable strategy. These findings highlight the importance of optimizing micro-relief construction and mulch application to enhance erosion control and support the recommendation of LBTr-M, TTr-M, and ZTr-M as effective strategies. Conversely, FSPs-M and NTr-M proved less effective under higher rainfall intensities. These findings emphasize the need to optimize micro-relief construction and mulch application for erosion management, as well as suggest that such strategies could be applied to the Loess Plateau and other erosion-prone regions worldwide with similar climatic and topographic conditions.